A. 3.65 m/s^2

B. 5.34 m/s^2

C. 13.73 m/s^2

D. 19.45 m/s^2

The correct answer is C. 13.73 m/s^2.

I tried to solve it originally by starting with...

1. F = ma.

2. Plugging in F(buoyant) = m*a

3. F(buoyant) = (density of balloon)*(volume of balloon)*a

4. (density of air)*(volume of balloon)*g = (density of balloon)*(volume of balloon)*a

Then I solved for a. But this is wrong?

According to the text, you are supposed to solve this by finding F(buoyant). Then find F(gravity). Then, F(buoyant) - F(gravity) = F(remaining).

Then, solve for a in F(remaining) = m(balloon)*a.

How does this make sense? F(remaining) is just a value indicating how much F(buoyant) exceeds F(gravity).